Desenvolvimento e avaliação biológica de novos aceptores de Michael: dipeptídeos miméticos, 3,5-bis(arilideno)piperid-4-onas e síntese inédita das pubesamidas A e B - Ruth Pereira Paulino (2024)
Michael acceptors are compounds that exhibit various biological activities described in the literature, such as anticancer, antimalarial, leishmanicidal, antiviral, and antiAlzheimer. This class is also known for its ability to form a covalent bond with cysteine, which enables the inhibition of certain proteins containing this amino acid. The first chapter of this work describes the design and synthesis of 15 new cinnamic acid derived mimetic dipeptides (24a-o, serie 1), a classic naturally occurring Michael acceptor, with overall yields ranging from 19-44%. Additionally, nine 3,5- bis(arylidene)piperidin-4-one compounds (25a-i, serie 2), containing a 1,2,3-triazole ring, were synthesized with overall yields ranging from 15-50%. Three compounds from series 1 (24a, 24e, and 24o) were tested against the SARS-CoV-2 virus, and 15 compounds from series 1 (24a-o) were tested against breast cancer cell lines (MCF-7and MDA-MB-231). None of the compounds tested showed significant activity against SARS-CoV-2 infected cells. Among the compounds tested against cancer cells, the Michael acceptor 24f exhibited the highest cytotoxicity against MDA-MB-231 cells (IC50= 2.5 µM) and a high selectivity index (7.9). In the second chapter, the novel synthesis of two naturally occurring Michael acceptors is presented: pubesamides A and B, which are N-benzoyltyramide compounds isolated from Casimiroa pubescens, a tropical fruit tree known for its psychotropic properties. The natural products were synthesized through a route in which the key step was a cross-metathesis reaction between a 1,1-disubstituted alkene and a dienone, in the presence of the second generation Hoveyda-Grubbs catalyst, giving both natural products on an overall yield of 12%. This study also involved the structural confirmation of both natural products using ¹H and ¹³C NMR spectroscopic techniques.